PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN METODE NUMBER HEAD TOGETHER DI KELAS V SDN 131/II SKB: PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN METODE NUMBER HEAD TOGETHER DI KELAS V SDN 131/II SKB - RANDI EKA PUTRA - SISKA (Jurnal Tunas Pendidikan, 2021)
The problem in this study is the students’ activities and learning outcomes is still low in mathematics at Class V SD Negeri 131/II SKB, this is evidenced by the results of premilinary observations made by the researchers the result is from 27 students only 30% students achieve the KKM. The reason is because teacher only use lecture methot that did not make students’ interested in learning. The purpose of this study was to describe and know about the implementation of the number head together in increasing the result of learning activities an class V. This study is kind of classroom action research (CAR). This study consisted of 2 cycles, each cycle carried out through 4 stages, namely planning, action, observation and reflection and consisted of 2 meetings. The results of this study indicate that based on observation of cycle I for learning 1 from the aspect of teachers 75% and 85% for learning 2 while in cycle II 90% for learning 1 and 90% for learning 2. On the participant aspect students cycle I 67% for learning 1 and 74% for learning 2 while in second cycle 81% for learning 1 and 85% for learning 2. The application of the number head together method in learning in first cycle is still not optimal. This can be seen from the test of the results of the test in first cycle only 74% of students who met the curriculum and in second cycle there was an increase of 85% of student who fulfilled the curriculum.